Legal Perspectives on Debtor's Responsibility in Fiduciary Guarantee Violations Under the Inbezitstelling Doctrine - Azizah, Azizah; Surahmad, Surahmad (DiH: Jurnal Ilmu Hukum, 2025)
A fiduciary guarantee is a type of special guarantee based on article 1132 which is included in material guarantees interpreted as absolute rights. In Indonesia, there are cases of default committed by debtors against debtors on fiduciary guarantees. Among the incidents that took place in Indonesia is the case in Decision Number 27/Pdt.G.S/2022/PN SGN. In this case, default occurred because the debtor did not fulfill his obligation to pay installments 3 times and did not hand over the fiduciary guarantee object after defaulting in paying off his debt. The urgency of this research is related to the responsibility of the defaulting debtor and the handover of the fiduciary guarantee object based on the legal principle of guarantees, namely the principle of inbezitstelling. To analyze this case, a qualitative method and a normative juridical approach were used by applying the Case Approach, the Legislation Approach, and the Conceptual Approach. This is because this research is based on doctrine, library sources and analyzes real cases that are related to the law. The creditor's rights are not fulfilled by the debtor based on the principal agreement between the two parties, so that the debtor must fulfill the principal agreement in the form of handing over the fiduciary guarantee object.